2011
DOI: 10.1002/cpa.20377
|View full text |Cite
|
Sign up to set email alerts
|

A note on Prandtl boundary layers

Abstract: This note concerns nonlinear ill-posedness of the Prandtl equation and an invalidity of asymptotic boundary layer expansions of incompressible fluid flows near a solid boundary. Our analysis is built upon recent remarkable linear illposedness results established by Gérard-Varet and Dormy and an analysis by Guo and Tice. We show that the asymptotic boundary layer expansion is not valid for nonmonotonic shear layer flows in Sobolev spaces. We also introduce a notion of weak well-posedness and prove that the nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 10 publications
0
123
0
2
Order By: Relevance
“…It is widely known that the mathematical study of Prandtl boundary layers and the inviscid limit problem is challenging due to its characteristic nature at the boundary (that is, v = 0 at y = 0) and the instability of generic boundary layers ( [6,7,8,9]). Here, for steady flows, we are able to justify the Prandtl boundary layer theory.…”
Section: Main Results and Discussionmentioning
confidence: 99%
“…It is widely known that the mathematical study of Prandtl boundary layers and the inviscid limit problem is challenging due to its characteristic nature at the boundary (that is, v = 0 at y = 0) and the instability of generic boundary layers ( [6,7,8,9]). Here, for steady flows, we are able to justify the Prandtl boundary layer theory.…”
Section: Main Results and Discussionmentioning
confidence: 99%
“…The result of [48] on the ill posedness for the linearized Prandtl equations is strengthened in [61,51], where it is shown that the solutions to the non-linear Prandtl equations cannot be Lipschitz continuous with respect to the initial data in Sobolev spaces. Moreover, it is proved by [61] that in the Sobolev framework one cannot expect a natural estimate of the asymptotic boundary layer expansion for the Navier-Stokes flows, if the leading term in the boundary layer is a non-monotonic shear layer flow as in [48].…”
Section: Ill-posedness Results For the Prandtl Equationsmentioning
confidence: 99%
“…Moreover, it is proved by [61] that in the Sobolev framework one cannot expect a natural estimate of the asymptotic boundary layer expansion for the Navier-Stokes flows, if the leading term in the boundary layer is a non-monotonic shear layer flow as in [48].…”
Section: Ill-posedness Results For the Prandtl Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…• even when one can construct it, the approximate solution can be unstable [15], [20] Therefore, for the Navier-Stokes equation with Dirichlet boundary condition, the justification of the inviscid limit is known only in the analytic framework [32]. Nevertheless, we point out that the above approach is efficient even for general quasilinear hyperbolic-parabolic systems (thus also for compressible fluids and MHD equations) when the boundary is non-characteristic (this happens for example with injection or succion boundary conditions), in this case the size of the boundary layer is ε (in the ansatz (2.1), V depends on z/ε) or in dimension one.…”
Section: Boundary Layersmentioning
confidence: 99%